Lenticulostriate Arteries and Basal Ganglia Changes in Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy, a High-Field MRI Study - Ling, Chen; Fang, Xiaojing; Kong, Qingle; Sun, Yunchuang; Wang, Bo; Zhuo, Yan; An, Jing; Zhang, Wei; Wang, Zhaoxia; Zhang, Zihao; Yuan, Yun (Frontiers in Neurology, 2019)
Background and purpose: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) mainly affects the cerebral small arteries. We aimed to analyze changes in the lenticulostriate arteries (LSAs) and the basal ganglia in patients with CADASIL using high-field magnetic resonance imaging (7.0-T MRI). Methods: We examined 46 patients with CADASIL and 46 sex- and age-matched healthy individuals using 7.0-T MRI. The number and length of the lenticulostriate arteries (LSAs), and the proportion of discontinuous LSAs were compared between the two groups. The Mini-Mental State Examination score, the modified Rankin Scale, the Barthel Index, and the MRI lesion load of the basal ganglia were also examined in patients with CADASIL. We analyzed the association between LSA measurements and the basal ganglia lesion load, as well as the association between LSA measurements and clinical phenotypes in this patient group. Results: We observed a decrease in the number of LSA branches (t = -2.591, P = 0.011), and an increase in the proportion of discontinuous lenticulostriate arteries (z = -1.991, P = 0.047) in patients with CADASIL when compared with healthy controls. However, there was no significant difference in the total length of LSAs between CADASIL patients and healthy individuals (t = -0.412, P = 0.682). There was a positive association between the number of LSA branches and Mini-Mental State Examination scores of CADASIL patients after adjusting for age and educational level (β = 0.442; 95% CI: 0.095, 0.789; P = 0.014). However, there was no association between LSA measurements and the basal ganglia lesion load among CADASIL patients. Conclusions: 7.0-T MRI provides a promising and non-invasive method for the study of small artery damage in CADASIL. The abnormalities of small arteries may be related to some clinical symptoms of CADASIL patients such as cognitive impairment. The lack of association between the LSA measurements and basal ganglia lesion load among the patients suggests that changes in the basal ganglia due to CADASIL are caused by mechanisms other than anatomic narrowing of the vessel lumen.